Pediatric ocular myasthenia gravis: Case report and literature review (2019)
Objective: The objective was to describe a case of ocular myasthenia gravis (MG) in a pediatric patient. Design: This is a descriptive, retrospective study and case report. Methodology: For the purpose of the case report, we searched and analyzed the literature referring to the diagnosis and treatment of ocular MG (OMG) in children. Description: A previously healthy 5‑year‑old girl presented to the emergency room because of sudden‑onset ptosis of the right upper lid without other symptoms. Her examination demonstrated fluctuating ptosis and limitation to downgaze in the right eye. Because of the fluctuation of the ptosis, OMG was suggested, and the patient was tested with ice‑pack test and neostigmine test with positive results. Treatment with pyridostigmine was initiated with a good response. Discussion: OMG has a very low incidence in pediatric patients. It is a disorder characterized by impairing neurotransmission at the neuromuscular junction that generates extraocular muscle weakness. It is important that ophthalmologists have knowledge about this disease because it is a differential diagnosis when there is a patient who has ptosis, strabismus, or limitation of movements. There are no standard diagnostic criteria for this disease; the diagnosis is based on clinical presentation and pharmacologic, serologic, and electrophysiologic tests. The treatment is based on steroids and anticholinesterase drugs. Some patients will require plasmapheresis or immunomodulators.